Analisis Strategi Digitalisasi Pembiayaan pada KSPPS BMT Dana Ukhuwah Cicalengka - Abdul Hakim; Alan Rusdiana; Rosti Setiawati; Riski Cahyawati; Ahmad Nurkamali (Prodi Ekonomi Syariah Universitas Majalengka, 2026)
The digitalization of financing in Islamic cooperatives has become a critical issue in improving service efficiency, expanding access, and enhancing the competitiveness of microfinance institutions. However, prior studies have predominantly focused on technological aspects without integrating compliance with Sharia principles in financing contracts. This study aims to analyze strategies for optimizing the digitalization of financing at KSPPS BMT Dana Ukhuwah, Cicalengka Branch, and to identify the inhibiting factors. The research questions address how digitalization strategies can be optimized and what challenges are encountered in their implementation. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the digitalization of financing has not been fully optimized due to limited managerial accuracy, insufficient human resources, and low levels of members’ technological literacy. The novelty of this study lies in the integration of digitalization strategies with compliance to Sharia contract principles. The study recommends enhancing human resource capacity, improving digital literacy among members, and strengthening Sharia-based digital systems.